2012
DOI: 10.4273/ijvss.4.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Automated Fibre Placement Parameters on Manufacturing Defects in Laminated Composites

Abstract: Composites are being continuously used to fulfil the demands for lighter and high performance components. Automated Fibre Placement is used as a technique to achieve best results to manufacture complex composite parts. However, this process induces some defects such as gaps, overlaps and tow drops in the manufactured laminate. This paper presents the influence of the manufacturing parameters such as feed rate, tow temperature, tow tension, and compaction pressure on the manufacturing induced defects in the lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…However, the demands of quality, repeatability, and accuracy of laying restrict high‐level lay‐up speeds 29 . Based on the lay‐up speed values studied in the literature, the lay‐up speed limits are determined as 0.1 and 0.4 m/s for low and high lay‐up speeds, respectively 30 …”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the demands of quality, repeatability, and accuracy of laying restrict high‐level lay‐up speeds 29 . Based on the lay‐up speed values studied in the literature, the lay‐up speed limits are determined as 0.1 and 0.4 m/s for low and high lay‐up speeds, respectively 30 …”
Section: Experimental Methodsmentioning
confidence: 99%
“…29 Based on the lay-up speed values studied in the literature, the lay-up speed limits are determined as 0.1 and 0.4 m/s for low and high lay-up speeds, respectively. 30 CF/PEKK composite laminates were manufactured by Coriolis C1 (Coriolis Composites) laser-assisted AFP system with a KUKA QUANTEC KR210R3100 robot with different process parameters given in Table 2 with the dimensions of 40 Â 60 Â 3 ± 0.1 mm 3 by laying up 20-layer CF/PEKK tapes onto a heated stainless steel tool at 130 C. The tool surface was covered with a 50 μm thick polyimide film (Thermalimide RCBS, Airtech Advanced Materials, UK) to ensure the easy separation of laminate. To control the temperature during laying, seven thermocouples connected to the control unit were placed in the tool corners.…”
Section: Manufacturing Of Composite Laminates With Afpmentioning
confidence: 99%
“…Bottenea et al. 12 presented the influence of feed rate, tow temperature, tow tension, and compaction pressure on gaps and overlaps in the laminate. Results revealed that gaps and overlaps were possible to be minimized or avoided by controlling above manufacturing parameters.…”
Section: Introductionmentioning
confidence: 99%